Managing patients' data with clinical decision support systems: a factual assessment. Issue 3 (3rd July 2018) - Razmak, Jamil; Bélanger, Charles H.; Farhan, Wejdan
ABSTRACT: In assessing the benefits of using e-health systems, the main goal of this study is to evaluate the real use of the clinical decision support system (CDSS) between 2007 and 2014 in Canada's healthcare sector. The quantitative method was based on data collected by the National Physician Survey in Canada. Results indicate that 63.8% of healthcare providers were using a CDSS at work in 2014 to help them in the decision-making process, a six-fold improvement since 2007. As for usage rate by sex, we found a statistically significant difference between men and women, with women from the Canadian physicians' group reporting greater CDSS use than men. In all age groups, a higher percentage of younger physicians used a CDSS in their practice. A number of suggestions are put forth to improve technological infrastructure and reduce the gap among age groups, genders and specialties.